Studi Analitis tentang Peran Media dalam Menciptakan Krisis: Perspektif Badan Administratif di Klub Olahraga - Fuad Abdul Mahdi Mahmoud Al-Hamdani; Maysoon Abdul Jalil Abdul Hassan; Rawaa Abdul Ameer Abbas (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to explore the role of sports media in creating crises that boxers may face, many journalists have failed to realize the dual role of the media in creating and managing crises. The media not only reports events but also acts as a key organizer in crisis preparation and management. Materials and methods. The researchers employed a descriptive survey method, correlational relationships, and standard studies on a sample of (79) administrative members from boxing clubs in the southern provinces of Iraq out of a total population of (270). The researchers selected the sample deliberately and developed the research scale. After applying the scale to the main experimental sample, the results were collected and processed using SPSS. The findings suggest that the role of the media is not to create crises in sports environments, both specific to sports and in general society. Results. The media role in creating crises is perceived as having a low value from the perspective of administrative bodies. Simultaneously, this value is considered unsatisfactory, given that the media's duty is to contain and manage crises in line with the public interest, without exaggeration or exacerbation. Media also plays a significant and effective role in crisis management in general, particularly in the crises faced by boxers and the administrative bodies of sports clubs dedicated to this sport. This is attributed to the influential role of media in the sports community and society at large, facilitated by the rapid dissemination of news and its impact on society, whether positively or negatively. Conclusion. The scale used in the study proves to be a valuable tool for detecting the level and role of media in creating crises, according to the perspectives of administrative body members in boxing clubs. The highest percentage for the sample in the scale of the media's role in creating crises was at a moderate level.